Civilian Counsel in General Court-Martial Cases Under the Uniform Code of Military Justice - John S. Sellingsloh; Kenneth J. Hodson (Washington University Law Quarterly, 1952)
This article is written with the view of acquainting civilian lawyers with some of the procedural aspects of the trial and appellate review of general court-martial cases under the Uniform Code of Military Justice, as implemented by the Manual for Courts-Martial, United States, 1951. Although every person in the armed forces is entitled to be represented without cost before a general court-martial and during subsequent appellate proceedings by a legally qualified military counsel, a number of such persons have elected to retain civilian lawyers as their representatives. As the number of persons subject to military law increases during the present period of partial military mobilization, it is reasonable to expect that more civilian lawyers will be retained to defend accused persons at the trial level and to represent them before the boards of review of the armed forces and the United States Court of Military Appeals.
Keywords: Courts-martial